Could Towel bath reduce aggressiveness in patient with dementia? Results from a crossover trial - Roberta Lodini; Stefano Terzoni; Agostino D'Antuono; Elena Sala; Giancarlo Celeri; Mauro Parozzi; Paolo Ferrara; Laura DiPrisco; Lara Carelli; Giada Cocciolo (Milano University Press, 2022)
BACKGROUND: Bathing is one of the most intimate activities during which persons with dementia are cared for. The literature suggests that 20-40% of patients with cognitive impairment, hospitalized in long-term facilities, may react with aggressive behaviours. AIM: To evaluate the efficacy of the towel bath technique in reducing agitation, aggression, and discomfort in nursing home residents with dementia. MATERIALS AND METHODS: An Inteentional crossover study was conducted; a convenience sample of patients with dementia,  was enrolled. Aggressive behaviors were evaluated using the italian version of the Care Recipient Behavior Assessment (CAREBA- ita). RESULTS: 71 resident were enrolled. Towel Bath technique showed a reduction in episodes of aggression and in the execution time of the procedure with a statistically significant difference (p < 0.05). CONCLUSIONS:  The technique Towel bath provides a viable alternative to traditional bath to reduce aggression in patients with dementia.